POTABILIDADE BACTERIOLÃ“GICA DA ÃGUA DE POÃ‡O OU DE FONTE DA ZONA RURAL DE PIRACICABA - Vertoni, Paulo CÃ©sar; Gallo, ClÃ¡udio Rosa; Nogueira, CecÃlia Helena (REVISTA DE AGRICULTURA, 2015)
POTABILIDADE BACTERIOLÃ“GICA DA ÃGUA DE POÃ‡O OU DE FONTE DA ZONA RURAL DE PIRACICABA